Design and implementation of planning information systems at the meso-micro levels a case of Region IV - Abad, Teresita G. 1948-
attempts to develop planning-oriented information systems were premised on the assumption that available data were of the quality required for formulating and updating regional plans. programs and policies. the study of focused on the development of a requisite information system that could respond to the requirements of regional and subregional level and planning. it was conceived as "diagnostic" in nature to enable identification of problems attendant to both data production and utilization; and, to provide provide empirical basis for guiding the design and implementation of the system as perceived by the responding planners. Regions IV was chosen as the study regions as it represents a microcosm of philippine region planning realities. Its heterogeneity in terms of geographic location and development (macro), subnational (meso) and local (micro) development planning. the research provided insights into the problems of the data production and the data utilization as seen from varying planning standpoints (municipal, city, provincial). these were looked into to gauge the planner' perception of the "ideal" information system that could enjoy the support and commitment of planner at the regional subregional levels. Results of the study underscored the planners expression of of preference for a system geared toward Policy and strategy formulation and their predisposition to a modular type of information system. General considerations for designing and implementing the requisite information system were then evolved.